2004
DOI: 10.1111/j.1751-1097.2004.tb00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin and UV‐Light Based Pathogen Reduction: Extent and Consequence of DNA Damage at the Molecular Level

Abstract: We are developing a technology based on the combined application of riboflavin (RB) and light for inactivating pathogens in blood products while retaining the biological functions of the treated cells and proteins. Virus and bacteria reduction measured by tissue culture infectivity or colony formation with UV light alone and in combination with RB yield equivalent results. The effects of RB as a sensitizing agent on DNA in white cells, bacteria and viruses in combination with UV light exposure have been evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(139 citation statements)
references
References 50 publications
4
134
0
1
Order By: Relevance
“…In the Mirasol system, addition of riboflavin (vitamin B2) to platelet concentrate together with ultraviolet light exposure selectively enhances damage to the guanine bases in the DNA of pathogens, thus preventing their replication [19]. There is no removal step at the end of the process, so residual riboflavin and its photo-products remain in the platelet concentrate during storage.…”
Section: Pathogen Reduction Technologymentioning
confidence: 99%
“…In the Mirasol system, addition of riboflavin (vitamin B2) to platelet concentrate together with ultraviolet light exposure selectively enhances damage to the guanine bases in the DNA of pathogens, thus preventing their replication [19]. There is no removal step at the end of the process, so residual riboflavin and its photo-products remain in the platelet concentrate during storage.…”
Section: Pathogen Reduction Technologymentioning
confidence: 99%
“…It has been demonstrated that combined application of Riboflavin and UV light could inactivate viruses and bacteria. These effects are the consequence of damage of DNA at the molecular level such as damage to the guanine bases in DNA induced by Riboflavin/UV light [15]. It has also been shown that riboflavin/UVlight induces a photochemical inactivation of viruses and bacteria in platelet concentrates, fresh frozen plasma and in red blood cells [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…These effects are the consequence of damage of DNA at the molecular level such as damage to the guanine bases in DNA induced by Riboflavin/UV light [15]. It has also been shown that riboflavin/UVlight induces a photochemical inactivation of viruses and bacteria in platelet concentrates, fresh frozen plasma and in red blood cells [15][16][17]. Antimicrobial efficacy of riboflavin/UV-A combination for bacterial isolates has been tested in vitro [18].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the pathogen's cell walls caused by massive amounts of reactive oxygen species. 14,15 3. Changes in the tertiary structure of the surrounding stromal collagen fibers, making it difficult for the collagenases to dock to their cleavage sites and exert their function.…”
Section: The New Term: Pack-cxl For Infectious Keratitismentioning
confidence: 99%